Model potencjału wirtualizacyjnego przedsiębiorstwa - Dzidowski, Adam (Model of Enterprises' Virtual Potential, 2009)
Virtual organization is defined as a dynamic coalition of autonomous enterprises based on continuous reorganization of structure and scope of business activity pursuing common market opportunities. This model of organizational structure numbers among novel, alternative theories of enterprise and redefines the paradigms of creating competitive advantage. Its entire concept fulfills the need for gathering resources and competencies effectively. Consequently the issue of creating virtual organizations can play a significant role for Polish enterprises operating in dynamic and distributed global markets. The analyses performed showed that ICT infrastructure, business trust and core competencies determine the possibility of creation of virtual organization. The significant effect resulting from these analyses is the model of Enterprises' Virtual Potential. This concept constitutes a tool for specifying to what degree the given network of enterprises is ready to become a virtual organization and what position the particular firms will hold. The results achieved from the survey of chosen group of Polish companies revealed particular barriers of creating virtual organizations in Poland. Overcoming these barriers might contribute to the development of virtual organizations in Poland. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 374-380